P-16 Clarifying the role of the hospice in support and assessment of carers and developing best practice. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Hearnshaw, Clare; Hewitt, Claire; Barber, Kim; Kassernoff, Jason; Taylor, Elaine; Playford, Debbie
Abstract : In 2015, five hospice representatives across Hertfordshire and Bedfordshire met as a 'meet and finish' group to review the service that hospices and palliative care providers give to carers. The aims of the group were to identify: Gaps in provision Types of assessment tools used Key learning from other services The need for services to collectively to reach more people. The types of hospice support for adult family carers within the Hospice UK (2013) document "Supporting family carers: report on the evidence of how to work with and support family carers to inform the work of the Commission into the Future of Hospice Care" were used as a basis of the discussion: Information, training and education – moving and handling, disease process, prognosis, specific care tasks, medication, dying Supportive activities – Drop in sessions, self-help groups, walking or activity groups, volunteer visiting, art-making groups Therapeutic activities – one-to-one counselling, therapeutic support groups, drama, music or art therapy, relaxations or mindfulness classes, complementary therapies and psychotherapy. The focus group ascertained that hospices are confidently providing therapeutic activities, however, they were less confident that hospices provide sufficient information, training and education and supportive activities for carers. Outcome: The group agreed to produce a minimum standard for specialist palliative care providers/hospices in meeting carers' needs. Minimum standard for supporting carers by specialist palliative care providers/hospices Signpost those early in the trajectory to partner organisations Young carers Carer Support Needs Assessment Tool Moving and handling, the care towards the end of life and Caring in Confidence courses Leaflets and website Financial or benefit advice Supportive activities Therapeutic activities.